Tracing Metadiscursive Stance over Time and Across Disciplines: A Comparative Study of English Research Articles - Esmat Babaii; Mahmood Reza Atai; Vali Mohammadi (Issues in Language Teaching, 2016)
Research in academic writing has revealed a strong tendency on the part of writers to interactively communicate their scientific findings with their readers. In doing so, the writers should take a position while arguing their propositions. This interaction as proposed by Hyland (2005b) takes places having two sides of stance and engagement. This study targeted the stance component of writer-reader interaction by integrating Hyland’s (2005b) and Hyland and Tse’s (2005a) frameworks to survey lexical and grammatical stance markers in the major subsections of English research articles in anthropology, education, horticulture, and zoology. The corpus included 240 English research articles published during two periods, namely, 1990 and 2010; 60 from each field, 30 articles from 1990 and 30 from 2010 yielding a total number of 1,270,021words. The findings suggested that stancetaking is a common feature of academic writing in the sampled disciplines regardless of the nature of the discipline. Also, hedges ranked first on the list of frequency count. Furthermore, there was a decreasing pattern in the use of stance markers highlighting a convergence among the scholars of the fields with respect to the totality of the facts established day by day. Then, some implications are drawn with plausible applicability in academic writing and EAP syllabus design.